Molecular analysis of community-acquired methicillin-resistant Staphylococcus aureus isolated from skin and soft tissue infections, Botucatu Medical School, Brazil - Favero Bonesso, M. [UNESP]; Faccioli-Martins, P. Y. [UNESP]; Alencar Marques, S. [UNESP]; Ribeiro de Souza da Cunha, M. L. [UNESP]; MendezVilas, A. (World Scientific Publ Co Pte Ltd, 2012)
Community acquired methicillin Staphylococcus aureus (CA-MRSA) was first reported in 1981, infecting people without risk factors. These strains harbor the Staphylococcal Cassette Chromosome mec (SCCmec) type IV, which contains the mecA gene codifying for methicillin resistance. CA-MRSA strains usually carry PVL (Panton-Valentine Leukocidin), a virulence factor responsible for tissue invasion, causing systemic infections and leading to serious complications. The aims of this work were to detect the mecA gene, SCCmec characterization and to detect the PVL gene of the S. aureus strains isolated from patients diagnosed with skin and soft tissue infections attending the Dermatology Service, of the Botucatu Medical School, Brazil. Among 127 collected samples, 66 (51.9%) were S. aureus and, from these, 7 (10.6%) harbored mecA gene, 3 (42%) with cassette type IV, and none of these samples carried the PVL gene, but it was detected in 10 (15.1%) samples of S. aureus methicillin sensitive (MSSA). Our study suggests the S. aureus strains that harbor PVL gene and MRSA are present in the community as important pathogens.
Keywords: Staphylococcus aureus; CA-MRSA; skin infections; PVL; SCCmec